STUDENTS’ PERSPECTIVES ON THE PRACTICES OF ONLINE PEER- FEEDBACK IN EFL WRITING CLASS - Arina Shofiya (Jurnal Bahasa Lingua Scientia, 2021)
Along with the development of educational technology, online peer feedback becomes an alternative in giving feedback. The flexibility in implementing the feedback makes it popular among the teachers. The activities in giving feedback can be practiced out of the classroom hours. However, the students may have different perspective on such practice. Listening to their voice will provide some insights in designing better online peer feedback. The findings of the present study reveals that the students perceive the practice of online peer feedback positively as it can improve their reading and writing skills. In addition, the practicality in utilizing the application can foster students’ motivation. Despite the fact that the accuracy of the feedback is not high, the practice of online feedback sparks students’ engagement in writing process.